Maternal perinatal mental health: Associations with bonding, mindfulness, and self‐criticism at 18 months’ postpartum - Brassel, Alexandra; Townsend, Michelle L.; Pickard, Judy A.; Grenyer, Brin F. S. (Infant mental health journal, 2020)
ABSTRACT The perinatal period is a time of significant transition for women, with changes in maternal mental health from pregnancy to 18 months’ postpartum. This study specifically analyzes maternal self‐criticism and mindfulness during pregnancy and at 18 months’ postpartum, and their associations with bonding. A longitudinal study (30 weeks’ gestation–18 months’ postpartum) assessed 32 mother–infant dyads, examining changes in maternal depression, anxiety, self‐criticism, and mindfulness. In addition, associations between maternal variables during pregnancy and bonding were investigated. Maternal depression and self‐criticism significantly increased from pregnancy to postpartum. Maternal anxiety, self‐criticism, and facets of mindfulness during pregnancy were also associated with mother–infant bonding at 18 months. Maternal mental health during pregnancy is subject to change postchildbirth. The lack of control and autonomy accompanying motherhood may result in an increase in self‐criticism during this period. Such feelings may elevate a woman's vulnerability to postpartum depression and have consequences for later maternal bonding. Early identification of at‐risk mothers is important to increase likelihood of positive outcomes. RESUMEN Trasfondo: el período perinatal es un momento de significativa transición para las mujeres, con cambios en la salud mental materna a partir del embarazo hasta los 18 meses después del parto. Este estudio específicamente analiza la auto‐crítica y la plena atención maternas durante el embarazo y a los 18 meses después del parto y sus asociaciones con la vinculación afectiva. Método: un estudio longitudinal (gestación de 30 semanas a 18 meses después del parto) evaluó a 32 díadas madre‐infante por medio de examinar cambios en cuanto a depresión materna, ansiedad, auto‐crítica y plena atención. Adicionalmente, se investigaron las asociaciones entre las variables maternas durante el embarazo y la vinculación afectiva. Resultados: la depresión materna y la auto‐crítica aumentaron significativamente desde el embarazo hasta después del parto. También se asociaron la ansiedad materna, la auto‐crítica y facetas de la plena atención durante el embarazo con la vinculación afectiva entre madre e infante a los 18 meses. Discusión: la salud mental materna durante el embarazo está sujeta a cambiar después del nacimiento del niño. La falta de control y autonomía que acompaña a la maternidad pudiera resultar en un aumento en la auto‐crítica durante este período. Tales sentimientos pudieran incrementar la vulnerabilidad de una mujer con respecto a la depresión posterior al parto y tener consecuencias más tarde en la vinculación afectiva materna. Es importante la temprana identificación de madres bajo riesgo para aumentar la probabilidad de resultados positivos. RÉSUMÉ Contexte: La période périnatale est un moment de transition importante pour les femmes, avec des changements dans la santé mentale maternelle de la grossesse à 18 mois après la naissance. Cette étude analyse plus spécifiquement l'autocritique maternelle et la pleine conscience durant la grossesse et à 18 mois après la naissance, ainsi que leur lien avec la connexion. Méthode: Une étude longitudinale (30 semaine de grosses à 18 mois après la naissance) a évalué 32 dyades mère‐nourrisson, en examinant les changements dans la dépression maternelle, l'anxiété, l'autocritique et la pleine conscience. De plus les liens entre les variables maternelles durant la grossesse et la connexion ont fait l'objet de la recherche. Résultats : La dépression maternelle et l'autocritique ont fortement augmenté de la grossesse à la période postpartum. L'anxiété maternelle, l'autocritique et les facettes de pleine conscience durant la grossesse étaient également liées à la connexion mère‐nourrisson à 18 mois. Discussion: La santé mentale maternelle durant la grossesse peut changer après la naissance de l'enfant. Le manque de contrôle et d'autonomie qui accompagne la maternité peut résulter en une augmentation de l'autocritique durant cette période. De tels sentiments peuvent élever la vulnérabilité d'une femme à la dépression postpartum et avoir des conséquences sur la connexion maternelle ultérieure. Une identification précoce des mères à risque est importante afin d'augmenter les chances de résultats positifs. ZUSAMMENFASSUNG Perinatale psychische Gesundheit der Mutter: Assoziationen mit Bindung, Achtsamkeit und Selbstkritik 18 Monate nach der Geburt Hintergrund: Die perinatale Phase ist eine Zeit, die signifikante Veränderungen für Frauen bedeuten kann, einschließlich Veränderungen der psychischen Gesundheit der Mutter von der Schwangerschaft bis zum 18. Monat nach der Geburt. Diese Studie untersucht die Selbstkritik und Achtsamkeit von Müttern sowie ihre Assoziationen mit Bindung während der Schwangerschaft und im 18. Monat nach der Geburt. Methode: In einer Längsschnittstudie (30. Schwangerschaftswoche bis 18 Monate nach der Geburt) wurden 32 Mutter‐Kind‐Dyaden untersucht. Dabei wurden Veränderungen der mütterlichen Depressions‐ und Angstsymptomatik, Selbstkritik und Achtsamkeit untersucht. Zusätzlich wurden Zusammenhänge zwischen mütterlichen Variablen während der Schwangerschaft und Bindung untersucht. Ergebnisse: Depression und Selbstkritik der Mutter nahmen von der Schwangerschaft bis nach der Geburt signifikant zu. Mütterliche Angstsymptomatik, Selbstkritik und Achtsamkeitsaspekte während der Schwangerschaft waren ebenfalls mit einer Mutter‐Kind‐Bindung im Alter von 18 Monaten assoziiert. Diskussion: Die psychische Gesundheit, die die Mutter während der Schwangerschaft hat, kann sich nach der Geburt ändern. Der Mangel an Kontrolle und Autonomie, der mit einer Mutterschaft einhergeht, kann in dieser Zeit zu einer Zunahme der Selbstkritik führen. Solche Gefühle können die Anfälligkeit von Frauen für eine postpartale Depression erhöhen und später Konsequenzen für die mütterliche Bindung haben. Eine frühzeitige Erkennung gefährdeter Mütter ist wichtig, um die Wahrscheinlichkeit positiver Behandlungsergebnisse zu erhöhen. 抄録 母の周産期メンタルヘルス:産後 18 ヶ月の絆、マインドフルネス、自己批判との関連 背景: 女性にとって周産期は重要な変化の時期であり、妊娠から産後 18 ヶ月まで母親のメンタルヘルスは変化を伴う。本研究は妊娠から産後 18 ヶ月間の母の自己批判とマインドフルネス、そして絆との関連を特に分析する。 方法: 32 組の母子のペアを評価した縦断研究 (妊娠 30 週から産後 18 ヶ月) で、母の抑うつ、不安、自己批判とマインドフルネスの変化を調査した。加えて、妊娠中の母の変数と絆の関連を調べた。 結果: 母親の抑うつと自己批判は妊娠中から産後まで著しく増加した。妊娠期間中の母親の不安、自己批判とマインドフルネスの事実は 18 ヶ月の時点での母と子どもの絆にも関連した。 考察: 妊娠中の母親のメンタルヘルスは子どもが生まれた後の変化を受けやすい。母親であることのコントロールと自主性の欠如はこの時期の自己批判を増加させるかもしれない。そのような感情は女性の脆弱さを産後うつまで高め、その後の絆形成に影響を及ぼすかもしれない。リスクのある母を早く識別することは、よい結果をもたらす可能性を高めるために重要である。 摘要 母親圍產期心理健康: 與產後18個月的維繫丶內觀和自我批評的關聯 背景: 圍產期是女性的重要過渡時期, 母親的心理健康狀況從懷孕到產後 18 個月都有變化。這項研究專門分析孕婦在懷孕期間和產後 18 個月的自我批評和內觀, 以及他們與母嬰維繫的關聯。方法: 一項縱向研究 (從妊娠 30 周到產後 18 個月) 評估 32 個母嬰二元組, 檢查母親抑鬱丶焦慮丶自我批評和內觀的變化。另外, 還研究懷孕期和建立維繫期間母親變數的關聯。結果: 從懷孕到產後, 母親的抑鬱和自我批評明顯增加。母親在孕期的焦慮丶自我批評和內觀方面也與 18 個月的母嬰維繫相關。討論: 母親在懷孕期間的心理健康可能會在產後發生變化。隨著成為母親後的缺乏控制和自主權, 可能導致自我批評增加。這種感覺可能會提高女性在產後患上抑鬱症的機會, 並影響以後的母嬰維繫。早期識別高危母親對於增加正面結果至為重要。 ملخص الصحة النفسية للأمهات في فتره ما قبل الولادة: العلاقات مع تكوين الروابط واليقظة والنقد الذاتي في عمر 18 شهرا بعد الولادة الخلفية: فتره ما قبل الولادة هي مرحلة انتقالية كبيرة للمرأة ، حيث تواجه تغيرات في الصحة النفسية من الحمل إلى 18 شهرا بعد الولادة. وتحلل هذه الدراسة علي وجه التحديد النقد الذاتي للأمهات واليقظة اثناء الحمل وفي سن 18 شهرا بعد الولادة ، وعلاقة ذلك بتكوين الروابط. الطريقة: تم إجراء دراسة طوليه (30 أسبوعا من الحمل إلى 18 شهرا بعد الولادة) لتقييم 32 من ثنائيات الأمهات والرضع ، ودراسة التغيرات في الاكتئاب الأمومي ، والقلق ، والنقد الذاتي واليقظة . بالاضافه إلى ذلك ، تم التحقيق في العلاقات بين المتغيرات الأمومية اثناء الحمل وتكوين الروابط. النتائج: ازداد الاكتئاب الأمومي والنقد الذاتي زيادة كبيره من الحمل إلى ما بعد الولادة. وارتبط أيضا قلق الأمهات والنقد الذاتي وأوجه اليقظة اثناء الحمل بتكوين الروابط بين الام والرضيع في 18 شهرا. المناقشة: تخضع الصحة النفسية للأمهات اثناء الحمل للتغيير بعد الولادة. وقد يؤدي انعدام التحكم والاستقلال المصاحب للامومه إلى زيادة في النقد الذاتي خلال هذه الفترة. وقد ترفع هذه المشاعر من درجه تعرض المراه للاكتئاب بعد الولادة ولها عواقب علي الروابط الاموميه اللاحقة. ومن المهم التحديد المبكر للأمهات المعرضات للخطر لزيادة احتمال النتائج الايجابيه.